2019
DOI: 10.1158/0008-5472.can-18-1397
|View full text |Cite
|
Sign up to set email alerts
|

miR-146a Controls Immune Response in the Melanoma Microenvironment

Abstract: Micro-RNAs (miR) are small non-coding RNAs that regulate gene expression, post-transcription, and manipulate immune responses in different types of cancer. In this study, we identify miR-146a as a negative regulator of immune activation, comparable to immune checkpoint molecules. miR-146a levels were increased in melanoma microenvironmental tissue, and miR-146a-/- mice survived longer and developed less metastases in comparison to wild type melanoma-bearing mice. T cells isolated from miR-146a-/- mice revealed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 28 publications
3
47
0
Order By: Relevance
“…In tumors, increase of IFN-g would lead to activation of the STAT3 pathway and was accompanied with increased expression of PD-L1, which was associated with poor prognosis of lung cancer [35]. IFN-g could also significantly inhibit the growth of B16 cells and increase the expression of PD-L1 by activating the STAT1 signaling pathway after treating B16 melanoma cells with IFN-g. After PD-1 antagonist was given to melanoma-bearing mice, the tumor suppressive effect of IFN-g was further enhanced [36]. In our experiments, DHA treatment significantly increased expression of IFN-g and phosphorylation of STAT1.…”
Section: Discussionsupporting
confidence: 50%
“…In tumors, increase of IFN-g would lead to activation of the STAT3 pathway and was accompanied with increased expression of PD-L1, which was associated with poor prognosis of lung cancer [35]. IFN-g could also significantly inhibit the growth of B16 cells and increase the expression of PD-L1 by activating the STAT1 signaling pathway after treating B16 melanoma cells with IFN-g. After PD-1 antagonist was given to melanoma-bearing mice, the tumor suppressive effect of IFN-g was further enhanced [36]. In our experiments, DHA treatment significantly increased expression of IFN-g and phosphorylation of STAT1.…”
Section: Discussionsupporting
confidence: 50%
“…STAT1 usually acts as the transcriptional factor in the tumor immune function [27][28][29]. Studies demonstrated that STAT1 is the functional target of miRNAs [30][31][32] (miRNA-145-5p, miRNA-146A, miRNA-21), but the regulation of miRNA-382-3p and STAT1 remain unclear. To verify if STAT1 was the functional target of miR-382-3p, we first examined the expression and correlation of them.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of miR-589 promotes cancer malignancy by increasing PD-L1 expression level (Liu et al, 2017). miR-146a, which is increased in metastatic melanoma, induces immune evasion of melanoma cells (Mastroianni et al, 2019). The combination of a miR-146a inhibitor and anti-PD-L1 improves survival in a mouse model of melanoma (Mastroianni et al, 2019).…”
Section: Discussionmentioning
confidence: 99%